DAYA TERIMA PRODUK OLAHAN REMPEYEK DAUN KERSEN (Muntingia calabura L) SEBAGAI SNACK HERBAL MASYARAKAT LOKAL - Anilia Ratnasari (Gema Wiralodra, 2019)
The amount of food or snacks that contain preservatives or chemicals consumed by the community, therefore, requires innovation and creation in food or herbal snacks made from local raw materials as consumption of the local community. This study aims to determine the acceptability of processed leaves of kersen leaves as a herbal snack for the local community. The method used was Randomized Block Design (RBD) with three samples A (young cherry leaf chips), B (medium cherry leaf chpis), and C (old cherry leaf chips) repeated 3 times. The instruments used were organoleptic test or sensory evaluation, by means of a value-differentiation test and hedonic scale test, with parameters of the quality of crispness, taste, color, and preference. The panel used by 35 untrained panelists namely the public and students as invited guests at the exhibition of products field lecture in Cikedung Indramayu West Java District. From the results of the power test, the kersen leaf chips which has the best percentage is medium-sized kersen leaf processed products with a crisp quality level of 51.42%, flavor (not bitter) 37, 14%, color (slightly brownish) 37.14%, and preference (somewhat like) 45.71%. Therefore, it is necessary to diversify food or snacks especially those that have nutritional value, are easy, economical, made from local resources, and can be used as entrepreneurial opportunities for the community.